Polygamy in the Digital Era: Comparison of Moderate and Conservative Views on Portal-Islam.id, NU.or.id, Rumaysho.com, and Muslim.or.id - Yoga Purnama; Anisa Maharani (Indonesian Journal of Islamic Law, 2023)
Polygamy is a controversial topic that has sparked debate among Indonesian society, especially in the digital era. This research aims to compare moderate and conservative views on polygamy presented by four popular Islamic websites in Indonesia: Portal-Islam.id, NU.or.id, Rumaysho.com, and Muslim.or.id. Using content analysis methods, this research explores the narratives formed by each website regarding the practice of polygamy. The research results show that NU.or.id places more emphasis on aspects of justice and women's welfare, while Portal-Islam.id and Rumaysho.com focus on religious legitimacy and the husband's obligations in polygamy. Muslim.or.id provides a more balanced view, but still faces challenges in balancing moderate and conservative views. This research also reveals that polygamy has complex social and psychological impacts, often detrimental to women and children in polygamous families. These findings emphasize the need for critical evaluation and a more inclusive approach in discussing and regulating polygamy practices in Indonesia, especially in the digital context.